External and Internal Stimuli-Responsive Metallic Nanotherapeutics for Enhanced Anticancer Therapy - Mohapatra, Adityanarayan; Uthaman, Saji; Park, In-Kyu (Frontiers in Molecular Biosciences, 2021)
Nanotherapeutics based on therapeutic, diagnostic, and imaging approaches offer distinct advantages in cancer treatment. Various nanotherapeutics have been presented as potential alternatives to traditional anticancer therapies such as chemotherapy, radiotherapy, and surgical intervention. Notably, the advantage of nanotherapeutics is mainly attributable to their high specificity toward cancer cells, where regular therapeutics fail to discriminate between normal and cancer cells. The specific anticancer targeting ability afforded by nanotherapeutics can minimize systemic toxicity as well as unfavorable side effects during treatment. To date, numerous nanoparticle formulations have been developed for anticancer therapy and among them, MNPs reportedly demonstrate promising cancer therapeutic and diagnostic efficiency owing to their dense surface functionalization ability, size and shape-dependent optical responses, easy and cost-effective synthesis procedure, and multiple anticancer effects. Metallic nanotherapeutics can remodel the tumor microenvironment by changing unfavorable therapeutic conditions to therapeutically accessible conditions with the help of different stimuli, including light, heat, ultrasound, an alternative magnetic field, redox, and reactive oxygen species. The combination of metallic nanotherapeutics with both external and internal stimuli can be used to trigger the on-demand release of therapeutic molecules, augmenting the therapeutic efficacies of anticancer therapies such as photothermal therapy, photodynamic therapy, magnetic hyperthermia, sonodynamic therapy, chemodynamic therapy, and immunotherapy. In this review, we have summarized the role of different metallic nanotherapeutics in anti-cancer therapy, as well as their combinational effects with multiple stimuli for enhanced anticancer therapy.